Anti Tuberculosis Activity of Forest Kedondong (Spondias pinnata) Stembark Extract Against Multiple Drug Resistance (MDR) Strain of Mycobacterium Tuberculosis - Dwija, I.B.N. Putra; Anggraeni, Mita; Ariantari, Ni Putu (BALI MEDICAL JOURNAL, 2016)
Background: Forest Kedondong (Spondias pinnata) traditionally known as “loloh cemcem” and commonly used as a chronic cough remedy. Previous research showed that methanol extract of Forest Kedondong leaves active against MDR strain of Mycobacterium tuberculosis. The aim of this study were to determine the phytochemical constituent and anti tuberculosis activity of stem bark extract of this plant against MDR strain of M. tuberculosis. Method: Coarsely powder of Forest Kedondong stem bark was extracted successively with n-hexane, chloroform and 80% ethanol. Anti tuberculosis assay of chloroform and ethanol extract was conducted using proportion method with Lowenstein-Jensen medium within 3 different concentration of extract of 1, 10, and 100 mg/mL. Activity was evaluated by inhibition of extract against M. tuberculosis growth, which was calculated by mean reduction in number of colonies on extract containing medium compared to control. Results and Discussion: Phytochemical test showed that chloroform extract contains terpenoid and flavonoids. Ethanol extract contains terpenoid, polyphenols and flavonoids. These extracts were active against MDR strain of M. tuberculosis with 100% inhibition at concentration of 100 mg/mL. Chloroform extract has higher inhibition against M. tuberculosis growth than Ethanol extract. Conclusions: These extracts were potentially developed to an anti tuberculosis constituent from natural product.